SEISMIC STRATIGRAPHY OF THE ADARE TROUGH AREA, ANTARCTICA - Whittaker J.M.; Müller R.D. (My University, 2006)
The Adare Trough, located 100 km NE of Cape Adare, Antarctica, is the extinct third arm of a Tertiary spreading ridge that separated East from West Antarctica. We use seismic reflection data, tied to DSDP Site 274, to link our seismic stratigraphic interpretation to changes in ocean-bottom currents, Ross Sea ice cover, and regional tectonics through time. Two extended unconformities are observed in the seismic profiles. We suggest that the earliest hiatus (early Oligocene to Mid-Miocene) is related to low sediment supply from the adjacent Ross Shelf, comprised of small, isolated basins. The later hiatus (mid-Miocene to late Miocene) is likely caused by strong bottom currents sourced from the open-marine Ross Sea due to increased Antarctic glaciation induced by mid-Miocene cooling (from Mi-3). Further global cooling during the Pliocene, causing changes in global ocean circulation patterns, correlates with Adare Basin sediments and indicate the continuing but weakened influence of bottom currents. The contourite/turbidite pattern present in the Adare Trough seismic data is consistent with the 3-phase contourite growth system proposed for the Weddell Sea and Antarctic Peninsula. Multibeam bathymetry and seismic reflection profiles show ubiquitous volcanic cones and intrusions throughout the Adare Basin that we interpret to have formed from the Oligocene to the present. Seismic reflection profiles reveal trans-tensional/strike-slip faults that indicate oblique extension dominated Adare Trough tectonics at 32-15 Ma. Observed volcanism patterns and anomalously shallow basement depth in the Adare Trough area are most likely caused by mantle upwelling, an explanation supported by mantle density reconstructions, which show anomalously hot mantle beneath the Adare Trough area forming in the Late Tertiary. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; PALEOCEANOGRAPHY; SEDIMENTARY; SEISMIC; Pliocene; Miocene; Oligocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен